Enhancing Sensory Attributes and Shelf Stability of Restructured Beef Steaks for Meat Value Addition - Basha M H S, Abrar; T, Sathu; V N, Vasudevan; A, Irshad; V L, Gleeja (Journal of Meat Science, 2026)
Achieving optimal tenderness and marketability of meat derived from aged animals with suboptimal characteristics is pivotal for enhancing meat value in the industry. Meat restructuring is a potent approach to attain this goal, primarily by formulating restructured beef steaks. These steaks are developed through a blend of type II (round and chuck in 1:1 ratio) and type III quality cuts (brisket, plate, and flank in a 1:1:2 ratio), acknowledged for their toughness. This study focused on standardising chunk size and the proportion of type II and type III quality cuts in restructured beef production, with a primary focus on assessing the shelf stability of the standardised product stored at deep freezer conditions for 60 days. The evaluation covers a broad spectrum of physico-chemical characteristics, TBARS, tyrosine, colour values, microbiological parameters, and sensory attributes. Our key findings unveil significant improvements in sensory attributes, increased pH, consistent cooking yield, and subtle variations in colour values and microbial counts, with the Restructured Beef Steaks (SRBS) consistently surpassing the control. Proximate composition, texture analysis, and shear force values further distinguish SRBS from the control. This research reinforces the feasibility of producing shelf-stable restructured beef steaks with superior sensory attributes, with a focus on a combination of 50% type II and 50% type III quality cuts. Vacuum tumbling is highlighted for its role in enhancing texture, tenderness, and cohesiveness, ensuring extended deep freezer storage without compromising sensory qualities. Additionally, the integration of microbial transglutaminase and mincing contributes to enhancement of sensory attributes.